2011
DOI: 10.1038/leu.2011.254
|View full text |Cite
|
Sign up to set email alerts
|

Clinical laboratory markers of inflammation as determinants of chronic graft-versus-host disease activity and NIH global severity

Abstract: Chronic graft versus host disease (cGVHD) remains a major cause of non-relapse morbidity and mortality after allogeneic hematopoietic stem cell transplantation. Currently there are no accepted measures of cGVHD activity to aid in clinical management and disease staging. We analyzed clinical markers of inflammation in the sera of patients with established cGVHD and correlated those with definitions of disease activity. 189 adults with cGVHD (33% moderate and 66% severe according to NIH global scoring) were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 49 publications
(63 reference statements)
8
58
0
Order By: Relevance
“…20 Chronic GvHD was categorized as active or not active, based on the clinician's therapeutic intent at the time of visit. 38 Pulmonary manifestations were captured by FEV-1 (forced expiratory volume in 1 second) and lung function score (based on FEV-1 and DLCO (diffusing capacity for carbon monoxide) adjusted for hemoglobin). The percentage of body surface area involved with cutaneous erythema, sclerosis and any involvement was documented by a dermatologist with expertise in cGvHD.…”
Section: Methodsmentioning
confidence: 99%
“…20 Chronic GvHD was categorized as active or not active, based on the clinician's therapeutic intent at the time of visit. 38 Pulmonary manifestations were captured by FEV-1 (forced expiratory volume in 1 second) and lung function score (based on FEV-1 and DLCO (diffusing capacity for carbon monoxide) adjusted for hemoglobin). The percentage of body surface area involved with cutaneous erythema, sclerosis and any involvement was documented by a dermatologist with expertise in cGvHD.…”
Section: Methodsmentioning
confidence: 99%
“…To perform Cox model analyses, we began with a large number of factors, which were specifically explored in this study, as well as several which were previously reported to be associated with survival in this cohort or the previous literature. 8,10 Factors under consideration included BSA % erythema, WBC, bilirubin, LFS, 4-point HCP global score, 11-point clinicianassessed global symptom severity score, KPS, eosinophil count, the interval from transplant to enrollment on the present study, walk distance in 2 min, platelet count, interval from cGVHD diagnosis to enrollment on the present study, age, type of cGVHD onset and NIH skin score. These parameters were then evaluated for their joint association with survival using a Cox proportional hazards model, with the final model determined by backward selection.…”
Section: Discussionmentioning
confidence: 99%
“…9 The following clinically important concurrent measures were recorded (referred to as 'outcomes of interest'): NIH global score as defined by Filipovich et al; 9 cGVHD activity by clinician therapeutic intent as previously defined by SA Grkovic et al; 10 Lee total symptom score; 11 and Short-Form 36 Health Survey physical component summary. Survival follow-up information was obtained by phone calls to the patients and their physician offices or by use of the Social Security death information website.…”
Section: Clinical Outcomes Measures and Survivalmentioning
confidence: 99%
“…Although malnutrition can reflect the severity of chronic GVHD in most patients, we also encounter patients who do not have a typical manifestation of chronic GVHD but lose body weight as in wasting syndrome. It is possible that subclinical inflammations after allogeneic HSCT lead to such a condition [94,95]. Although the most important intervention is the correct treatment of chronic GVHD itself, consulting NST is recommended when patients lose weight [96].…”
Section: Nutritional Management In Long-term Follow-up Unitmentioning
confidence: 99%